PERANAN KEPOLISIAN TERHADAP PELANGGARAN PENGGUNAAN JALAN UMUM UNTUK KEPENTINGAN PELAKSANAAN PESTA DIWILAYAH HUKUM KOTA PEKANBARU - Basri, Hasan; Ridwan, Mukhlis; *, Er (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
ABSTRACTThe use of the facilities or the road to self-interest must have a permit issued by the Police as a party is given the authority to issue licenses for the use of road traffic other than as stipulated in the Indonesian Police Chief Regulation No. 10 Year 2012 About Setting Traffic In Certain Circumstances in addition to the use of the Road Traffic events , people can use the highway to conduct an activity to the extent they have to get permission from the police . The purpose of writing this paper , First , The Role of the Police in granting permission for the use of public roads in the region law enforcement party Pekanbaru city ? Secondly, the effectiveness of the application of sanctions against violations of the use of public roads for the implementation of the party in reducing the occurrence of acts of violation of law in the region use public roads Pekanbaru city?This type of research is conducted legal research Sociological , while the population and sample an entire party is related to the problem under study , which used data sources , primary data , secondary data , and the data tertiary , data collection techniques in this study with interviews , questionnaires and literature study From the research, there are two main things that can be concluded . First , that the role of the Police in granting permission to use the road for the implementation of the party consists of granting or rejection , as well as disseminating regulatory Chief of Police of Indonesia Number 10 Year 2012 Second, the effectiveness of the application of sanctions against violations of the use of public roads for the implementation of the party had not been effective . advice authors , first , expected to police in giving permission should really factor memperhtikan road to be used for a party , and to always socialize again to the public about the regulations permit the use of the road . Second , are expected to police to take action against violations of the use of the road for the sake of the party.Keywords : Role - Against Police Abuse - Use Path - party interests